Presuppositions and shared knowledge in perception and production of business text - Shayakhmetova, Leysan; Zharkynbekova, Sholpan; Aimoldina, Aliya (Opción, 2019)
The study aims to investigate presuppositions and shared knowledge in perception and production of business text via comparative qualitative research methods. This study shows that in the perception and production of a business text in Kazakh, Russian and English, each business communicator has the sum of specific (communicative-pragmatic, encyclopaedic and linguistic) presuppositions and shared knowledge, which is characteristic of a given socio-professional and sociocultural context. In conclusion, a business specialist owns a set of professional and business skills, taken in a specific business context, which make this professional business community of communicants unique in their own way.